2019
DOI: 10.1158/0008-5472.can-18-0668
|View full text |Cite
|
Sign up to set email alerts
|

IDO1 and Kynurenine Pathway Metabolites Activate PI3K-Akt Signaling in the Neoplastic Colon Epithelium to Promote Cancer Cell Proliferation and Inhibit Apoptosis

Abstract: The tryptophan-metabolizing enzyme indoleamine 2,3 dioxygenase 1 (IDO1) is frequently overexpressed in epithelial-derived malignancies, where it plays a recognized role in promoting tumor immune tolerance. We previously demonstrated that the IDO1-kynurenine pathway (KP) also directly supports colorectal cancer growth by promoting activation of b-catenin and driving neoplastic growth in mice lacking intact adaptive immunity. In this study, we sought to delineate the specific role of epithelial IDO1 in colon tum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
133
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(142 citation statements)
references
References 55 publications
7
133
1
1
Order By: Relevance
“…Here, however, we demonstrate that Kyn plays a cell-autonomous role in maintaining colon cancer cell proliferation. Indeed, a recent study demonstrated that conditional knockout of the IDO1 gene specifically in colonic cells limits colon cancer development in mice (Bishnupuri et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, however, we demonstrate that Kyn plays a cell-autonomous role in maintaining colon cancer cell proliferation. Indeed, a recent study demonstrated that conditional knockout of the IDO1 gene specifically in colonic cells limits colon cancer development in mice (Bishnupuri et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer, IDO1 expression correlates with reduced tumor infiltration by lymphocytes, increased rates of hepatic metastases, and a poor clinical outcome (Brandacher et al 2006). Recently, it was shown that conditional deletion of IDO1 in colonic cells delays colon cancer in animal models (Bishnupuri et al 2019), indicating that Kyn levels are likely altered in colon cancer and may contribute to tumorigenesis.…”
mentioning
confidence: 99%
“…Moreover, signaling pathways such as Ras signaling pathway, MAPK signaling pathway, PI3K‐Akt signaling pathway, autophagy, JAK‐STAT signaling pathway and TGF‐β signaling pathway were also identified in the enrichment results. These pathways are critical and participate in a variety of cellular biology processes: the Ras signaling pathway directs cell migration and mediates cell apoptosis (Charest et al, 2010; Gulbins et al, 1995); the MAPK signaling pathway and PI3K‐Akt signaling pathway can promote cell proliferation (Bishnupuri et al, 2019; Y. Wang et al, 2011; Wu, Tan, Huang, Ong, & Shen, 2009); autophagy can alleviate intestinal damage caused by severe burns (D. Zhang, Qiu, Wang, et al, 2017), and the JAK‐STAT signaling pathway involves in promoting migration of intestinal epithelial cells (Le et al, 2016). Understanding the characterization of mRNAs helps us to study the function and characteristics of circRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 177 ] Kynurenine is known to promote intestinal epithelial proliferation and has been linked to inflammation, immune suppression, metabolic disease, psychiatric disorders, and even cancer. [ 178,179 ] Thus, it is interesting to speculate that increased gut microbiale tryptophan metabolism might actually be beneficial for healthy aging by counteracting the hyper‐proliferative effect of host‐derived kynurenine. In fact, a previous report states that indole derivatives produced by commensal bacteria can reduce frailty symptoms in old mice, as well as expand healthspan of worms ( Caenorhabditis elegans ) and flies ( Drosophila melanogaster ).…”
Section: Conclusion and Prospectsmentioning
confidence: 99%